Apical Hypertrophic Cardiomyopathy and Multiple Coronary Artery-Left Ventricular Fistulas: A Case Report. - Massimo Ruggiero; Francesco Tota; Marco Sassara; Nicola Locuratolo; Vito Calvani; Ilaria Dentamaro; Maria Tesorio; Pietro Scicchitano; Pasquale Caldarola; Marco Matteo Ciccone (Journal of Hypertension and Cardiology, 2013)
We describe a rare case of multiple coronary artery-left ventricular fistulas associated with apical hypertrophic cardiomyopathy in a 62 year asymptomatic old male admitted to our department for a perioperative evaluation of non cardiac surgery, already diagnosed for multiple coronary artery-left fistulae. He underwent transthoracic echocardiography and then to accelerated dipiridamole stress-echo.
Keywords: coronary artery left-ventricular fistulae